Revisiting Quantification of Phenylalanine/Tyrosine Flux in the Ochronotic Pathway during Long-Term Nitisinone Treatment of Alkaptonuria - Lakshminarayan R. Ranganath; Andrew T. Hughes; Andrew S. Davison; Milad Khedr; Richard Imrich; Mattias Rudebeck; Birgitta Olsson; Brendan P. Norman; George Bou-Gharios; James A. Gallagher; Anna M. Milan (Metabolites, 2022)
Changes in the phenylalanine (PHE)/tyrosine (TYR) pathway metabolites before and during homogentisic acid (HGA)-lowering by nitisinone in the Suitability of Nitisinone in Alkaptonuria (AKU) 2 (SONIA 2) study enabled the magnitude of the flux in the pathway to be examined. SONIA 2 was a 48-month randomised, open-label, evaluator-blinded, parallel-group study performed in the UK, France and Slovakia recruiting patients with confirmed AKU to receive either 10 mg nitisinone or no treatment. Site visits were performed at 3 months and yearly thereafter. Results from history, photographs of eyes/ears, whole body scintigraphy, echocardiography and abdomen/pelvis ultrasonography were combined to produce the Alkaptonuria Severity Score Index (cAKUSSI). PHE, TYR, hydroxyphenylpyruvate (HPPA), hydroxyphenyllactate (HPLA) and HGA metabolites were analysed by liquid chromatography/tandem mass spectrometry in 24 h urine and serum samples collected before and during nitisinone. Serum metabolites were corrected for total body water (TBW), and the sum of 24 h urine plus total body water metabolites of PHE, TYR, HPPA, HPLA and HGA were determined. The sum of urine metabolites (PHE, TYR, HPPA, HPLA and HGA) were similar pre- and peri-nitisinone. The sum of TBW metabolites and sum TBW + URINE metabolites were significantly higher peri-nitisinone (p < 0.001 for both) compared with pre-nitisinone baseline. Significantly higher concentrations of metabolites from the tyrosine metabolic pathway were observed during treatment with nitisinone. Arguments for unmasking of the ochronotic pathway and biliary elimination of HGA are put forward.